2019
DOI: 10.1055/a-1009-6671
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ECMO and Mortality in Neonates with Congenital Diaphragmatic Hernia Using the SNAP-II Score

Abstract: Background The mortality of neonates with congenital diaphragmatic hernia (CDH) ranges between 20 and 40% even in specialized high-volume centers. The Score for Neonatal Acute Physiology-II (SNAP-II Score) could facilitate the decision about supportive therapies in CDH newborns. Methods The SNAP-II score consists of the variables arterial blood pressure, pH, PaO2:FiO2, body temperature, diuresis, and seizure activity and was calculated at an age of 12 h. Results 101 CDH newborns treated in our institution betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…A prospective trial assessing the initial ventilation strategy in CDH infants showed the predictive value of SNAP-II for both mortality as well as the need for extracorporeal membrane oxygenation (ECMO) 40. The SNAP-II Score is easy to use and its potential as early predictor was also confirmed in a more recent retrospective study 41…”
Section: Delivery Room Management: Novel Conceptsmentioning
confidence: 94%
See 1 more Smart Citation
“…A prospective trial assessing the initial ventilation strategy in CDH infants showed the predictive value of SNAP-II for both mortality as well as the need for extracorporeal membrane oxygenation (ECMO) 40. The SNAP-II Score is easy to use and its potential as early predictor was also confirmed in a more recent retrospective study 41…”
Section: Delivery Room Management: Novel Conceptsmentioning
confidence: 94%
“… 40 The SNAP-II Score is easy to use and its potential as early predictor was also confirmed in a more recent retrospective study. 41 …”
Section: Delivery Room Management: Novel Conceptsmentioning
confidence: 99%
“…Nhiều nghiên cứu đã chứng minh được vai trò của thang điểm SNAP-II trong việc đánh giá tiên lượng tử vong trong nhiều bệnh lý như thoát vị hoành bẩm sinh, xuất huyết não, trẻ sinh non [8,9]. Điểm số SNAP-II trung bình của cả nghiên cứu là 29,9 ±12,3, cao hơn so với nghiên cứu của Narongsak Nakwan là 25,0 ±12,1 [11].…”
Section: Bàn Luậnunclassified
“…Management of newborn infants with CDH requires a high skill set, with multidisciplinary team involvement, starting from the point of antenatal diagnosis. Despite improved outcomes over the years [3], morbidity and mortality remain high (20-40%), even in high volume tertiary referral centers [4,5]. A quarter of survivors suffer neurodevelopmental impairment involving all domains, and ranges from motor and sensory (hearing, visual) deficits to cognitive, language, and behavioural impairment [6].…”
Section: Introductionmentioning
confidence: 99%